Parâmetros para avaliação do serviço de iluminação pública: benchmarking do processo de gestão no município de Catu – Bahia - SANCHEZ, Francisco Fidalgo (2016)
This paper addresses the issue of public lighting in the municipal perspective, seeking to evaluate the current efficiency of the systems to the regulatory nuances in the sector and the threats and opportunities in the management of parks. The asymmetry of information between the players: utility, contractors and municipal administration, is contextualized throughout the text, relating to specific regulatory issues and know-how required for effective reduction. Although more extensive field research focused on data obtained in the city of CATU-BA, with benchmarking creation process focused on the analysis of four large blocks: registration management, measurement of storage, control of consumer bills and implementation of maintenance and expansion services, obtaining perfectly replicable criteria to other municipalities in addition to the processes necessary to improve management and efficiency of the public lighting system.